Fazlur Rahman's Perspective on Hadith Critical Reposition - Gufron, M. (Millati: Journal of Islamic Studies and Humanities, 2022)
Fazlur Rahman is an insider who has critical ideas about hadith. The reason is that there is a very long interval between the time of the Prophet Muhammad SAW. with the bookkeeping of hadith, as well as debatable about the concept of sunnah-hadith that is still not finished yet. The method used in this research is descriptive-analysis with a hermeneutic approach. According to Rahman, there is a fundamental difference between the definition of sunnah and hadith. Sunnah is a living tradition in society while hadith is a reportage of sunnah. This research is used library research, namely documentation data. The researcher uses descriptive-analytical method, with a hermeneutic approach. The main points of Rahman's thoughts related to the history of the development of hadith are comprehensive and strict. Then, the hermeneutic approach is used to explain the concepts or theories that are initially unclear related to the concept of sunnah-hadith become clear. The results of this study reveal that Rahman differentiates the concept of sunnah (conceptual sunnah) with the content of sunnah (literal sunnah). The earlier finds absolutes, and the last is more or less dependent (relative). According to Rahman, what distinguishes universal normative principles is the first sunnah. On the other hand, the literal sunnah allows us to understand the logical ratio behind the general principles contained in the conceptual sunnah. Thus, that binds us to obey Rasulullah PBUH, the Messenger of Allah is a conceptual sunnah, not a literal sunnah.